Exfoliation and alignment of h-BN for thermal application - Teo, Jing Xiang (Nanyang Technological University, 2022)
Innovative upstream technologies have led to advancements in technology. Since the dawn of video graphics, GPU and CPU speed have grown significantly from a few GFLOPS to hundreds of GFLOPS and soon in the thousand range. This is made possible when billions of transistors are squeezed onto a single computer chip. This would increase the chip’s density significantly and enable a faster and more powerful computer to be made possible. Processing Chipsets are more compact and capable of higher processing speed; thus, a higher-efficiency and thinner heat spreader are in demand. It also creates localized hot spots on the chips because of the high-power loading in a limited space. Thus, a considerable power density can be attained when operating the device if not dealt with, which would result in overheating and then slows down the chipset processing efficiency, making them inefficient. Over time this hot spot can lead to degrading factors such as delamination, creep, corrosion, and electro-migration. Thus, efficient thermal management is critical for the performance of modern electronics. Efficient heat spreaders are made from materials with high thermal conductivity such as copper and aluminium. Emerging nonmetal two-dimensional boron nitride (BN) shows great promise for heat spreader thanks to its very high thermal conductivity and excellent electrical insulation. BN is a graphene-like materials in sheet form, resulting in intrinsically high surface area that is important for heat speeder. However, only the in-plane thermal conductivity of BN is high while the out-of-plane thermal conductivity is low. Therefore, it is important to achieve an alignment of BN sheets along the direction of heat spreading path. To enable the full potential of the thermal properties, layered (few) h-BN-nanosheets have to be extracted from h-BN (bulk) powder. It is also noteworthy that the uniqueness and potent characteristics of functionalized h-BNNS like enhanced solubility in liquid, stability, and excellent biocompatibility have also led to specific extensive applications to be made possible, such as improved thermal conductivity (film method or Thermal paste method) and novel polymeric composites. This project conducts a study of assembling h-BN nanosheets through exfoliation and the application of magnetic alignment. Its properties, such as microplate-formed structure and separating capabilities, open up special applications. H-BN has excellent thermal conductivity and low thermal expansion and density; it has excellent thermal shock properties. Various exfoliation methods have been employed and analysed, from dispersion of pristine h-BN in the ethanol-water mixture and other techniques involving the Leiden-frost effect to allow for water surface tension. Pristine Exfoliated h-BN with a mean size of 100nm was mixed with ferrofluid to create a hybrid solution capable of magnetic alignment. After that, various methods were employed to form a freestanding film for thermal analysis